Το μοντέλο Sachdev-Ye-Kitaev - Θεοφιλόπουλος, Δημοσθένης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2018)
The subjects of this Master thesis is to study the Sachdev-Ye-Kitaev (SYK) model, focusing on the Conformal Field Theory aspect, viewing it through the AdS/CFT correspondence. This particular model presents some very interesting features and thus attracted a lot of attention. It is now solved and there is ongoing research for its bulk dual. To begin, the two-point and four-point functions are presented and from the latter the operators of the model are deduced. These Green’s functions are studied in the IR limit where conformal symmetry is emergent. Then, the 6-point and 8-point functions are presented along with their features that make the model solvable. Moreover, the effective action of the model and its symmetries are discussed along with certain reparametrizations and their physical meaning as Nambu-Goldstone modes. After presenting their Schwarzian action and a brief introduction to the quantum butterfly effect, the chaotic behaviour of the model is discussed. Finally, a brief discussion concerning the bulk dual and SYK-like models is presented. In the appendices, an introduction to conformal symmetry and the OPE expansion is given and also technical computations are included.